On domination of nonlinear wave interaction in the energy balance of wind-driven sea - Zakharov, V.E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
Here some aspects of the physics of wind-driven sea are investigated theoretically. It is demonstrated that theeffective four-wave nonlinear interaction plays the leading role in the formation of the spectra of turbulent waves. In particular this interaction leads to non-linear damping which exceeds standard data at least by the order of magnitude. The theory developed here is compared with the available experimental data.